Empowering Urban Diplomacy: Surabaya’s Sister City Collaboration with Kitakyushu, Japan for Sustainable Development - Dzazira, Rasta Hayuning; Pratama, Dhani Putra (Journal of Paradiplomacy and City Networks, 2023)
This research examines the dynamic paradiplomacy practices of Surabaya City Government through its robust Sister City cooperation with Kitakyushu, Japan, forged since 1997. Paradiplomacy, as a guide for foreign policy conducted by sub-national actors, provides a platform for cities to engage in international networks and pursue their interest. By applying the International Cooperation Theory and Concepts of Paradiplomacy, this study employs a descriptive qualitative research approach with literature study and interviews to analyze the successful implementation of this collaboration. The research focuses on the city’s concerted efforts towards achieving a Green Sister City status, aligning with the Sustainable Development Goals and promoting environmental sustainability. Surabaya’s paradiplomatic endeavors complement the national diplomatic efforts, showcasing Indonesia’s rising regional government’s role in international affairs. The study highlights the significance of urban diplomacy in driving sustainable development initiatives through cross-border collaborations.